Penggunaan Algoritma random forest dan Agile scrum dalam Pengembangan Aplikasi Kesehatan mental Berbasis Web 'MentalWell' - Masbahah, M; Putri, Azzahra Kareena Rendri; Lathifa, Diana; Nawang, Diah Munica; Anshori, Fauzi Ihsan; Kusnadi, Bimo Adji (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Teenage mental health is a major concern today. Teenagers often suffer from various mental health problems such as depression, anxiety, and stress, which can have a negative impact on their development and lives. The aim of this research was to develop a mental health website that helps adolescents identify and overcome mental health problems. The "MentalWell" website uses a random forest algorithm to classify youth mental health questionnaires and provide appropriate intervention recommendations. This website was created using the System Development Life Cycle (SDLC) method with an Agile Scrum approach, based on a design that was carried out using the React.js framework for the front-end and CodeIgniter 4 (CI4) for the back-end. In the Agile scrum model, software development is divided into short iterations called sprints. Each sprint involves sprint planning, daily scrum, sprint review, and sprint retrospective. The main steps in the process of classifying mental health disorders using the random forest algorithm, starting from data collection to testing and final results. Testing uses the black box method, with valid results for all features developed.